Biosynthesis of chain‐specific alkanes by metabolic engineering in Escherichia coli. Issue 1 (20th October 2015) - Yan, Hong; Wang, Zheng; Wang, Fang; Tan, Tianwei; Liu, Luo
Abstract : Renewable energy is one of the key issues for sustainable development. Compared with alcohols and esters, alkanes—with the highest energy density—are a better liquid fuel. In this study, we focused on medium‐chain alkanes, the main compounds of jet fuels. To control the chain length of alkanes, a chain length specific thioesterase from Umbellularia californica, a fatty acyl‐CoA reductase Acinetobacter sp. M‐1 that prefers lauroyl‐CoA and myristoyl‐CoA, and a decarbonylase from Nostoc punctiforme were engineering into Escherichia coli cells. The combination of genes, which determines the chain length of products, was carefully designed to control the product spectrum. Undecane and tridecane were produced with a concentration of 2.21 ± 0.18 and 1.83 ± 0.12 mg⋅g −1, respectively. A total of 4.01 ± 0.43 mg⋅g −1 pentadecane was also detected in the final products. The results showed the feasibility to use microorganisms as cell factories for alkane production. The product spectrum revealed that the chosen genes played a key role in the production of chain length specific alkanes.